ENSURING THE STATE'S ECONOMIC SECURITY AND TODAY'S CHALLENGES (Development Service Industry Management, 2024)
The article is devoted to the study of the issue of economic security of the state and highlighting its current issues in modern conditions of martial law. Since ensuring economic security is one of the most important national priorities. Based on the research conducted, the content and components of economic security are revealed, the main factors influencing its formation in war conditions, the main risks and threats that have arisen for domestic enterprises and the state are identified, in particular, physical destruction of infrastructure, shortage of qualified labor, risks to food security and challenges for the functioning of the national economy in conditions of constant military operations. One of the components of national economic security is the economic security of domestic enterprises. The main threats to the economic security of domestic enterprises engaged in foreign economic activity before the start of the full-scale war were considered by most scientists to be: low competitiveness of domestic products, high energy and material intensity of the branches of the national economy, insufficient level of investment in the industry of Ukraine, lack of a mechanism for effective implementation of the latest technologies in industry, risky credit and monetary policy of the state in the banking sector, etc. Today, these challenges have not disappeared. However, more powerful and with a greater level of negative impact on both economic security and the functioning of the enterprise as a whole have appeared. Thus, with the start of the full-scale war, the issue of preserving production capacities became acute for many enterprises. The article considers the main areas of international support for stabilizing the economic security of Ukraine.
Keywords: economic security; war; components of economic security; enterprise; economic risks and threats